(untitled) (Jagannath University Journal of Arts, 2026)
The paper proposes to explore the empowerment of rural women in business in Bangladesh by participating in Small and Medium Enterprises (SMEs) through a Sociological perspective in regard to economic pursuits, social accountability, and cultural change. The ultimate goal is to examine the role of SME engagement towards the multidimensional empowerment of women, especially in addressing gender-based disparities, poverty, and socio-cultural limitations. The study has a qualitative approach based on thematic analysis. Using in-depth interviews, field observations, and demographic surveys, 50 rural women entrepreneurs with varied socioeconomic statuses were included in the study. The aim of the study was to learn how empowerment varies according to some factors, including marital status, education, family support, income level, and hardship experiences. Results show that women’s SME involvement results in a significant level and of economic and social empowerment of rural women. Women gained enhanced income, decision-making power in the homes, management of property and family wealth mobility and. The two diverse categories of women identified in the study are those who started their entrepreneurial career as a result of experiencing the acute social or financial difficulties, and those women who enjoyed better familial support. The theoretical contribution of the study lies in broadening the current knowledge on empowerment as a sociological process determined by structural and agency-related variables. In practical terms, it provides policy and development practitioners with information about how to create gender-sensitive SME initiatives that overcome the intersectional constraints that rural women experience. Jagannath University Journal of Arts, v-15, i-2, 2025:p92-107